Mind Mapping Techniques Are Useful to Improving the Learning Outcomes of Explanatory Text Material for Grade Vi Elementary School Students - Handayani, Menik; Wachid BS, Abdul; Saryono (International Journal of Educational Research Excellence (IJERE), 2025)
Teachers who still teach in a monotonous and lecture way, make students feel confused and their learning results decrease. In grade VI students, it is still found that students have not understood the core of the text, and have not been able to compile the core of the reading into a summary.  The summaries and explanatory texts made by students are also less than optimal. Aims: This study aims to examine the use of mind mapping techniques in improving the learning outcomes of explanatory text material in elementary schools. Method: Descriptive approaches and qualitative methods are used in this study. The sources of information came from interviews, observations, and explanatory text tests. Data analysis was carried out descriptively to describe students' ability to understand explanatory text material. Result: The results of the study showed that the learning outcomes of explanatory text material increased with the mind mapping technique in grade VI students in elementary schools. There was an increase in completeness from 2 students to 21 students and only 4 students did not complete. Conclusion: The conclusion of this study is that mind mapping techniques are more efficient and applicable in improving student learning outcomes in elementary school